Double-Lung Transplantation in a Patient with Pulmonary Type B Niemann-Pick Disease: A Valid Treatment Option. (27th April 2022) - Mora, Víctor Manuel; Osorio, Joy Selene; Iturbe, David; Tello, Sandra; Guzmán, Yedra; Sánchez, Laura; Gómez, José Javier; Cifrián, José Manuel
Abstract : Niemann-Pick disease is a rare autosomal recessive disease characterized by an abnormal intracellular lipid accumulation. Type B is later in onset and a less severe form of the disease, so affected people may survive in adulthood. Storage of sphingomyelin in pulmonary macrophages can lead to interstitial lung disease. There are very few published cases of lung transplantation in patients with Niemann-Pick disease, all of them described in the last 2 years. We present here one case of a 57-year-old man successfully treated with a double-lung transplant.